2011
DOI: 10.1103/physreve.83.021908
|View full text |Cite
|
Sign up to set email alerts
|

First-passage-time analysis of atomic-resolution simulations of the ionic transport in a bacterial porin

Abstract: We have studied the dynamics of chloride and potassium ions in the interior of the Outer membrane porin F (OmpF) under the influence of an external electric field. From the results of extensive all-atom molecular dynamics (MD) simulations of the system, we computed several first-passage-time (FPT) quantities to characterize the dynamics of the ions in the interior of the channel. Such FPT quantities obtained from MD simulations demonstrate that it is not possible to describe the dynamics of chloride and potass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Modulations in the available explored region lead to gradients in the system effective free energy, inducing a local bias in its diffusion that can promote a macroscopic net velocity for asymmetric channel profiles [7] or due to applied alternating fields [8]. Geometric barriers constitue a common feature at small scales; they are found in a variety of systems, including molecular transport in zeolites [9], ionic channels [10], or in microfluidic devices [11,12], where their shape explains, for example, the magnitude of the rectifying electric signal observed experimentally [13].…”
mentioning
confidence: 99%
“…Modulations in the available explored region lead to gradients in the system effective free energy, inducing a local bias in its diffusion that can promote a macroscopic net velocity for asymmetric channel profiles [7] or due to applied alternating fields [8]. Geometric barriers constitue a common feature at small scales; they are found in a variety of systems, including molecular transport in zeolites [9], ionic channels [10], or in microfluidic devices [11,12], where their shape explains, for example, the magnitude of the rectifying electric signal observed experimentally [13].…”
mentioning
confidence: 99%
“…This restriction can be understood as an effective change of the entropy of the Brownian ratchet as it displaces along the confined environment. 12 The relevance of entropic barriers to promote entropic transport 13,14 in confined environments has been recognized in a variety of situations that include molecular transport in zeolites, 15 ionic channels, 16 or in microfluidic devices, 17,18 where their shape explains, for example, the magnitude of the rectifying electric signal observed experimentally. 19 In fact, spatially varying geometric constraints provide themselves an alternative means to rectify thermal fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the coupling between the system and the geometrical constraints overimposed by the environment can be relevant in situations such as molecular transport in zeolites, 3 ionic channels, 4 or in microfluidic devices. 5,6 Moreover, geometrical constraints can induce novel dynamical scenarios, such as particle separation, 7 cooperative rectification, 8,9 and negative mobility 10,11 that are absent in the behavior of the corresponding systems in bulk.…”
Section: Introductionmentioning
confidence: 99%